STRATEGI VIRAL MARK ETING: ANALISIS FAKTOR-FAKTOR KEBERHASILAN KAMPANYE VIRAL DI TIKTOK PADA RATUBAGUS INDUSTRIES - Komang Hare Yashuananda; I Made Darmada; Ni Putu Loviana Riska; Nyoman Dwika Ayu Amrita (Journal of Innovation Research and Knowledge, 2026)
The rapid growth of short-form video–based social media platforms, particularly TikTok, has encouraged companies to adopt viral marketing strategies as an effective digital marketing approach. This study aims to analyze the factors influencing the success of viral marketing campaigns on TikTok at Ratubagus Industries. The research focuses on content characteristics, audience engagement (likes, comments, and shares), and the utilization of trends and the TikTok algorithm in enhancing campaign virality. This study employs a qualitative approach with a case study method. Data were collected through in-depth interviews, TikTok content observation, and relevant documentation. Data analysis was conducted using descriptive qualitative techniques, including data reduction, data presentation, and conclusion drawing. The findings indicate that the success of Ratubagus Industries’ viral marketing campaigns is driven by the synergy between authentic, relevant, and entertaining content, high levels of audience engagement, and the strategic use of trends and an understanding of the TikTok algorithm. Audience engagement serves as the primary driver of content dissemination, while trends and algorithms function to expand content reach organically. This study contributes theoretically to the development of viral marketing literature on social media and provides practical implications for companies in designing effective digital marketing strategies on TikTok